The association between ambient temperature and elite racewalking performance in the olympics and world championships - Zhang, Xiangning; Cui, Dandan; Jiang, Zili; Yang, Wenchao (Frontiers in Sports and Active Living, 2025)
IntroductionGlobal warming has become one of the major challenges in athletics, with evidence suggesting that racewalking is susceptible to high ambient temperature, though the magnitude of this relationship remains uncertain. This study aimed to investigate the relationship between weather conditions and racewalking performance in major international events, and examine differences across sex, performance levels, and race segments.MethodsData on results, ambient temperatures, and relative humidity were collected from eight events over ten years for women's and men's 20 km and men's 50 km racewalking. Statistical analysis included the coefficient of variation (CV) for performance stability and Welch's ANOVA for event comparisons. Correlation analysis was used to examine the relationship between weather conditions and performance, while Generalized Linear Models (GLMs) identified key variables associated with performance across various factors.ResultsThe women's 20 km had the highest performance stability (CV = 4.89%); other disciplines were also stable (CV < 10%). Ambient temperature significantly correlated with finishing times (r = 0.38–0.92, p < .05), but relative humidity showed minimal correlation (r = −0.48, p < .05). GLMs showed ambient temperature was associated with performance, with varying sensitivity across events: finishing time increased by +1.15%/°C, +0.96%/°C, and +0.77%/°C per degree t rise in temperature, respectively. The top8 athletes in women's 20 km had stronger associations (+0.64 to +0.67% vs. +0.42%), while athletes below 4th in men's 20 km showed higher sensitivity (+0.74% to +1.33%). All athletes in 50 km exhibited pronounced trends (start: −1.44 to −3.14%; end: +2.43 to +4.64%). The model showed a stronger association between ambient temperature and racewalking performance in the first half (pseudo R2 = 0.30–0.74 vs. 0.11–0.28).ConclusionThe racewalking performance of elite athletes shows correlation with ambient temperatures, especially in the first half, with these associations varying by sex, performance levels, and race segments. These findings underscore the necessity for athletes and coaches to develop individualized, segment-specific pacing and thermal management strategies to optimize performance in thermally challenging conditions.